Mengulik Kontribusi Media Digital dalam Memaksimalkan Pelayanan di Lingkup Gereja Pentakostal - Siburian, Ferry (Pusat Studi Pentakosta Indonesia, 2025)
The existence of digital media has greatly influenced the lives of today's humans, almost all areas of life have been elaborated with digital media ranging from buying and selling transactions, education, entertainment, family communication, to church life. This article is intended to explore the contribution of digital media in maximizing church services in the Pentecostal scope. Descriptive qualitative methods and literature reviews are used with the intention that the explanation related to the description of the influence of digital media in today's life, the description of the use of digital media in Pentecostal church services, and the contribution of digital media in maximizing servants in the Pentecostal church scope can be explained sequentially, systematically and in depth. It is concluded that digital media will contribute to maximizing services in the Pentecostal church scope because it has been proven to increase the abilities of God's servants, make services more relevant, a place to actualize themselves, and be able to expand the reach of services.AbstrakKeberadaan media digital sudah sangat mempengaruhi kehidupan manusia masa kini, nyaris seluruh area kehidupannya terelaborasi dengan media digital mulai dari transaksi jual beli, dunia pendidikan, hiburan, komunikasi keluarga, hingga kehidupan bergereja. Artikel ini dimaksudkan untuk mengulik kontribusi media digital dalam memaksimalkan pelayanan gereja di lingkup pentakostal. Metode kualitatif deskriptif dan kajian literatur yang digunakan dengan maksud agar penjelasan terkait deskripsi pengaruh media digital dalam kehidupan masa kini, deskripsi penggunaan media digital dalam pelayanan gereja pentakostal, serta kontribusi media digital dalam memaksimalkan pelayan di lingkup gereja penakostal dapat dijelaskan secara runut, tersistimatik dengan baik serta mendalam. Disimpulkan bahwa media digital akan berkontribusi memaksimalkan bagi pelayanan di lingkup gereja pentakostal karena terbukti meningkatkan kemampuan para pelayan Tuhan, menjadikan pelayanan lebih relevan, wadah untuk mengaktualisasi diri, serta mampu memperluas jangkauan pelayanan.